Yoga Theraphy Untuk Penyakit Diabetes Melitus - Wiasa, I Wayan (JURNAL YOGA DAN KESEHATAN, 2018)
Diabetes Mellitus disease or abbreviated as DM is one of the chronic diseases caused by carbohydrate, protein and fat metabolism abnormalities and the development of macrovascular and neurological complications. The disease is characterized by elevated blood glucose levels (hyperglycemia) and allows for a decrease in the ability to respond to insulin or decrease insulin formation by the pancreas. DM can attack anyone from adolescence to adulthood. This disease becomes one of the categories of diseases that are dangerous, because it becomes one of the causes of disability, chronic complications that can spread to the heart, blood vessels, kidneys, eyes and nerves, even this disease can lead to death. If not prevented as early as possible, people with Diabetes Mellitus will continue to increase throughout the year, especially with a fast-paced and instant life, causing a variety of stress and prolonged stress that also trigger the emergence of this disease. Various alternative healing options for patients such as a healthy diet, exercise, until the consumption of drugs. Among the ways of treatment, exercise or exercise is still in demand by most people, one of which is often incorporated yoga practice with meditation so-called yoga theraphy is a special yoga therapy for diabetics. Some studies reveal that the movements in yoga can overcome the problems experienced by diabetics, of course, through regular exercise and balanced with a healthy diet.